GLP-1RA versus placebo in patients with heart failure and mildly reduced or preserved ejection fraction: An updated meta-analysis of randomized controlled trials - Duhan, Sanchit; Kurpad, Krishna Prasad; Keisham, Bijeta; Shtembari, Jurgen; Brener, Alina; Kanakadandi, Uday B.; Garg, Anuj; Adoni, Naveed A.; Mehta, Sanjay S. (International journal of cardiology, 2025)
Currently, limited guideline-directed medical therapies are available for heart failure (HF) with preserved and mildly reduced ejection fraction (EF). Both are associated with an increased risk of hospitalization and death, especially in overweight, obese, or diabetic individuals. We searched Cochrane, Embase, and MEDLINE from inception to November 2024. Trials with HF patients randomized for GLP-1RA (glucagon-like peptide-1 receptor agonists) and reported adverse cardiovascular and mortality outcomes were included. Statistical analysis was performed using Cochrane Review Manager 5.4.1. 4474 patients with HF (preserved and mildly reduced EF) were included in the study. 2278 (50.91 %) received a GLP-1RA [either semaglutide (1914, 84 %) or Tirzepatide (364, 16 %)], and 2196 (49.01 %) received a placebo. GLP-1RA reduced the composite event of cardiovascular mortality and worsening HF exacerbation [139 vs. 194, RR: 0.64 (95 % CI: 0.45–0.92)]. However, on subgroup analysis, there was no significant difference in cardiovascular (CV) deaths [67 vs. 71, RR 0.89 (95 % CI: 0.65–1.24)]. The HF exacerbations were significantly reduced in the GLP-1RA group [83 vs. 138, RR 0.59 (95 % CI: 0.45–0.76)]. Kansas City Cardiomyopathy Questionnaire clinical summary score (KCCQ-CSS) was favorable for GLP-1RA [Std Mean Difference (SMD): 7.38 (95 % CI: 5.51–9.26)], reflected by an increase in 6-min walk distance in GLP-1RA groups [SMD: 17.69 (95 % CI: 11.87–23.34)] and contributed by a decrease in body weight in GLP-1RA groups [SMD -9.56 (95 % CI -12.74 to −6.39)]. GLP-1RA reduce HF exacerbations and can play a role in reducing hospitalizations, improving patient's functional status, and significantly impacting the global healthcare burden of HF. However, the current data does not indicate any overall mortality benefit. Created using Biorender.com Legend: GLP-1RA- GLP-1 receptor agonist, RR-risk ratio, SMD-standard mean difference, HF-heart failure, EF-ejection fraction, CV-cardiovascular, KCCQ-CSS- Kansas City Cardiomyopathy Questionnaire clinical summary score. Up arrow- higher, Down arrow- lower, green colored arrow- favorable outcome, red colored arrow- worse outcome. (For interpretation of the references to colour in this figure legend, the reader is referred to the web version of this article.) [Display omitted] •GLP-1RAs reduce the incidence of composite major adverse cardiovascular events in heart failure patients.•A significant improvement in quality of life is seen with GLP-1RA.•A statistically significant sustained weight loss occurs at 52 weeks.•Assessment of association with mortality needs more powered studies.